THE EFFECT OF SPELLING BEE GAME TOWARDS STUDENT’S VOCABULARY MASTERY OF EIGHTH GRADE STUDENTS AT SMP 18 IN BENGKULU CITY QUASI EXPERIMENT AT STUDENTS OF SMP NEGERI 18 KOTA BENGKULU - Gilang Redi Fadli; Ferri Susanto; Ali Akbarjono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to investigate the effect of the Spelling Bee Game on the vocabulary mastery of eighth-grade students at SMP 18 in Bengkulu City. This study was conducted based on the issue of low vocabulary proficiency among students, which is often caused by monotonous learning methods, the lack of interactive spelling activities, and students’ low motivation to learn new vocabulary. The research employed a quasi-experimental design using the Non-Equivalent Control Group Design, involving two classes with a total of 48 students. The instrument used was a vocabulary test assessing students’ spelling accuracy, word recognition, word meaning comprehension, and their ability to use vocabulary in simple contexts. The results demonstrate a significant disparity in post-test scores between the experimental and control groups, with mean scores of 53.50 and 74.50, respectively. The independent samples t-test showed a significance value of 0.000 (< 0.05), confirming that the Spelling Bee Game significantly improved students’ vocabulary mastery.